Twenty years of numerical syntaxonomy - Mucina, Ladislav; van der Maarel, E. (1989)
The development of numerical syntaxonomy during its first 20 yr is reviewed. The use of methods of numerical classification and ordination is the dominating feature of the development. National and local phytosociological data banks were established, large data sets handled and many important vegetation monographs were methodically based on multivariate data analysis. Particularly the development in Italy, the Netherlands, Czechoslovakia, and Sweden contributed to new theoretical elements of numerical syntaxonomy. Ordination became a common tool of searching for reticulate synsystematic relationsbetween community types. The most popular ordination techniques have been Principal Components Analysis and Detrended Correspondence Analysis. Hierarchical agglomerative techniques of clustering still prevail in classification, although the divisive strategy of TWlNSPAN has also become an effective tool for phytosociological clustering and table sorting. Extensive program packages, also for personal computers have now become standard equipment for many vegetation scientists.